2014
DOI: 10.1111/imj.12568
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of prevalence, disease characteristics and management of systemic lupus erythematosus in Australia: identifying areas of unmet need

Abstract: Background: Few epidemiological studies of systemic lupus erythematosus (SLE) have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 41 publications
2
28
1
Order By: Relevance
“…The prevalence of SLE in Aboriginal people living in the Darwin, Katherine and East Arnhem regions of the Northern Territory was estimated 20 years ago to be twice that of the non‐Aboriginal Australian population . Several other studies focusing on remote Australian populations have also identified a higher prevalence of SLE in Aboriginal compared with non‐Aboriginal people living in the same regions . One of the authors (PB) collected a database of SLE patients from 2009 to 2015, and estimated prevalence of SLE amongst Top End Aboriginal Australians to be 140 per 100 000 people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of SLE in Aboriginal people living in the Darwin, Katherine and East Arnhem regions of the Northern Territory was estimated 20 years ago to be twice that of the non‐Aboriginal Australian population . Several other studies focusing on remote Australian populations have also identified a higher prevalence of SLE in Aboriginal compared with non‐Aboriginal people living in the same regions . One of the authors (PB) collected a database of SLE patients from 2009 to 2015, and estimated prevalence of SLE amongst Top End Aboriginal Australians to be 140 per 100 000 people.…”
Section: Discussionmentioning
confidence: 99%
“…14 Several other studies focusing on remote Australian populations have also identified a higher prevalence of SLE in Aboriginal compared with non-Aboriginal people living in the same regions. 15 One of the authors (PB) collected a database of SLE patients from 2009 to 2015, and estimated prevalence of SLE amongst Top End Aboriginal Australians to be 140 per 100 000 people.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that patients with SLE feel misunderstood by their families, the community and even the specialists treating them [15]. Consequently, patients feel that their quality of life needs are not being met by treating teams [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Earlier studies described a high frequency of clinical manifestations of LN in IA patients, 2,3 but there are no data on the underlying renal histopathology in IA. 6 This study investigated the incidence, histological characteristics and clinical outcome of LN in the largest hospital of the Northern Territory (NT), Australia, where approximately 27% of the population identifies as IA. 7 …”
Section: Introductionmentioning
confidence: 99%